Impact of Educational Intervention on Cervical Cancer and HPV Vaccine Knowledge, Attitudes, and Acceptance among First-Year Medical Students of Birat Medical College - Guragain, Parth; Agarwal, Hulas; Niraula, Aarju; Bhagat, Baby; Chaudhary, Sarita; Kafle, Tara Kumari (Birat Journal of Health Sciences, 2024)
Introduction: Cervical cancer poses a significant health burden, particularly in developing nations, with notable incidence and mortality rates. However, there exists a notable gap in understanding the knowledge, attitudes, and acceptance surrounding cervical cancer and the Human Papillomavirus (HPV) Vaccine. This study aims to evaluate the current awareness, attitudes, and acceptance levels of HPV Vaccine among first-year medical students, alongside assessing the effectiveness of an educational intervention on these aspects. Objectives: To evaluate current knowledge, attitude and acceptance of cervical cancer and HPV Vaccine and evaluate the impact of educational intervention. Methodology: 2 An analytical cross-sectional study was conducted among 96 first-year medical students at a medical college in Nepal from December 24, 2023, to February 28, 2024, after receiving Ethical Approval. Total enumeration sampling technique was applied, and a structured self- administered questionnaire, validated for data collection, was employed. Data were collected at baseline and after an educational intervention class to assess the impact on the knowledge, attitude, and acceptance toward cervical cancer and the HPV Vaccine. Result: Pre-intervention scores (mean=5.90, SD=1.73) significantly increased after the intervention (mean=11.65, SD=1.44) with p<0.001, indicating a 97.46% increase. Willingness to receive HPV vaccination increased from 47.9% to 88.5%, and willingness to recommend vaccination increased from 88.54% to 96.88%. No significant differences were found in vaccination willingness. Conclusion: Educational interventions significantly enhanced medical students' willingness to receive and recommend HPV vaccination, suggesting potential for future healthcare provider influence on vaccination behaviors.